Lumbricus Rubellus Earthworm Extract Hydrogel for Treatment of Diabetic Ulcer Wounds - Diana Tri Lestari; Muhamad Jauhar; Eko Retnowati (Journal of Pharmascience, 2026)
A diabetic ulcer is a complication that requires serious treatment because it is the highest cause of amputation. This condition has an impact on the morbidity, mortality, and socioeconomics of people with diabetes. Therefore, accuracy is needed in managing diabetic ulcers, one of which is natural ingredients that have potential as topical ulcer medicines, namely the Lumbricus rubellus earthworm. This study aims to find out the most effective formula for the treatment of diabetic ulcer wounds. The formula for this drug candidate is made using the hydrogel preparation formulation using an HPMC 940 base with variations in the active ingredient of lumbricus worm extract of 20%, 50%, and 80% to obtain the desired hydrogel preparation. The candidate drug will be tested, namely physical tests including organoleptic tests, homogeneity tests, pH tests, viscosity tests, spreadability tests, and adhesive tests. After that in vivo trial using Wistar rat experiments. The results of the organoleptic test showed that the three formulas were in gel form with a distinctive extract odor, but the three preparations showed different colors, namely brownish yellow, dark brown, and blackish brown. The three formulations appear homogeneous, having a pH between 4.36 and 4.44 and a viscosity between 5,376 cp and 5,894 cp. The spreading power in formulas 2 and 3 is good, and formula 2 has good adhesion. The results of this study demonstrate that the group treated with 50% L. rubellus topical extract experienced the most significant and rapid wound healing among all intervention groups. L. rubellus extract can be used as a topical gel preparation for wound care, with the best formulation at a concentration of 50%.